FACTORS AFFECTING ENERGY EFFICIENCY IN EMERGING ECONOMIES: MIXED MODELS - Mustafa Akal; Çisem Bektur; Mustafa Naimoğlu (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study aims to explain energy efficiency by social, political, institutional, and economic variables for emerging countries during the 1990-2018 period. The estimated models exhibited cointegrated relationships. According to the predicted models, while GDP per capita and total factor productivity have the most positive effect on energy efficiency, on the other hand, fossil fuel use has the most negative effect on energy efficiency among economical variables. Social globalization, government efficiency, and control of corruption are positive; on the other hand, urbanization is negatively effective on energy efficiency.A 1% increase in GDP per capita improves the energy efficiency between 0.78% and 0.86%, and a 1% increase in total factor productivity increases it by about 0.48%. On the other hand, a 1% increase in fossil fuel consumption reduces energy efficiency between 0.56% and 0.70%. A 1% increase in the energy use of the service and industry sectors causes a decrease in the energy efficiency of about 0.43% and 0.19%, respectively. A 1% increase in social globalization, government efficiency, and control of corruption increase energy efficiency by about 0.15%, 0.10%, and 0.03%, respectively, while a 1% increase in urbanization decreases it by about 1.18%